Comparative Effects Of Gamma Rays, Low Energy Electron Beam And High Energy Electron Beam On Microbial Quality Of Cloves (Syzygium Aromaticum) - Ocloo, F.C.K.; Odai, B.T.; Darfour, B.; Torgby-Tetteh, W.; et al. (Discover Food, 2026)
Effects of gamma rays, high energy electron beam (HEEB) and low energy electron beam (LEEB) on the microbial quality of cloves is reported. Cloves were irradiated at 2, 4, 6, 8, and 10 kGy, while un-irradiated samples were used as controls. Treated samples were evaluated for Total Viable Counts (TVC), Total coliform counts, Staphylococcus aureus, Escherichia coli, Bacillus cereus, yeast and mould, and Salmonella spp. The presumptive organisms were isolated and identified. Irradiation reduced the microbial loads (TVC) to below detection limit at 8 kGy and total coliforms were reduced to below detection limit at 4 kGy. The bactericidal action of gamma ray and HEEB was comparable and more effective than that of LEEB. The most dominant isolate was Bacillus spp. LEEB has potential for surface microbial decontamination.
Research Article
Keywords: Contamination; Gamma rays; High and low energy electron beams; Pathogens